Current Variation Effect on Hardness and Corrosion Resistance of Formed Weld Layer - Syaripuddin; Sopiyan; Ahmad Nur Hisyam (Jurnal Konversi Energi dan Manufaktur, 2026)
Hardfacing over carbon steel was carried out using the SMAW apparatus. The sample was hard-faced with a single layer using HV 800 electrode with a 1G weld position. Different welding currents were used, such as 90, 100, and 110 A. After the weld, the sample was quickly immersed in distilled water. Cooled samples were cleaned with a chipping hammer and a wire brush. Afterwards, the samples were cut for hardness and corrosion testing. The highest hardness in the sample was welded using 110A, while the lowest hardness was welded using 90A. Increasing the current from 90 to 110 A could increase hardness by approximately 2.31%. The lowest current was used during welding, resulting in a lower corrosion rate. This means that the welding layer produced at the lowest current has greater corrosion resistance than that produced at higher currents. Reducing the current from 110 to 90 A could reduce the corrosion rate by approximately 44.33%. Finally, all three specimens meet the "good" criteria of corrosion resistance.